The Role of Street Art as a Language of Innovation in Uzbekistan’s Architectural Practices (Architecture Image Studies, 2024)
This research covers the intersection of street art and architectural practices in Uzbekistan, focusing on how street art acts as a language of innovation within the urban landscape. By analyzing historical, sociocultural, and artistic developments, the research provides evidence that street art is a transformative medium that bridges traditional Uzbek aesthetics with the demands of contemporary architecture. This paper draws on primary and secondary sources, including case studies of the street art festival and historic district revitalization projects in Tashkent, to illustrate how street art contributes to urban identity, inclusiveness, and creativity. The paper adopts an interpretive approach to underline challenges and opportunities regarding the integration of street art into architectural practices and positions it as a critical tool for fostering urban regeneration and cultural engagement in post-Soviet Uzbekistan.